Characteristics of Ventricular Tachycardia Ablation in Patients With Continuous Flow Left Ventricular Assist Devices. (June 2015) - Sacher, Frederic; Reichlin, Tobias; Zado, Erica S.; Field, Michael E.; Viles-Gonzalez, Juan F.; Peichl, Petr; Ellenbogen, Kenneth A.; Maury, Philippe; Dukkipati, Srinivas R.; Picard, Francois; Kautzner, Josef; Barandon, Laurent; et al.
Abstract : Background—: Left ventricular assist devices (LVADs) are increasingly used as a bridge to cardiac transplantation or as destination therapy. Patients with LVADs are at high risk for ventricular arrhythmias. This study describes ventricular arrhythmia characteristics and ablation in patients implanted with a Heart Mate II device. Methods and Results—: All patients with a Heart Mate II device who underwent ventricular arrhythmia catheter ablation at 9 tertiary centers were included. Thirty-four patients (30 male, age 58±10 years) underwent 39 ablation procedures. The underlying cardiomyopathy pathogenesis was ischemic in 21 and nonischemic in 13 patients with a mean left ventricular ejection fraction of 17%±5% before LVAD implantation. One hundred and ten ventricular tachycardias (VTs; cycle lengths, 230–740 ms, arrhythmic storm n=28) and 2 ventricular fibrillation triggers were targeted (25 transseptal, 14 retrograde aortic approaches). Nine patients required VT ablation <1 month after LVAD implantation because of intractable VT. Only 10/110 (9%) of the targeted VTs were related to the Heart Mate II cannula. During follow-up, 7 patients were transplanted and 10 died. Of the remaining 17 patients, 13 were arrhythmia-free at 25±15 months. In 1 patient with VT recurrence, change of turbine speed from 9400 to 9000 rpm extinguished VT. Conclusions—: Catheter ablation of VT among LVAD recipients is feasible and reasonably safe even soon after LVAD implantation. Intrinsic myocardial scar, rather than the apical cannula, seems to be the dominant substrate.